URGENSI PEMBAHARUAN HUKUM PIDANA TERKAIT DENGAN KEBIJAKAN HUKUM PIDANA PADA PERTANGGUNGJAWABAN PIDANA KEJAHATAN KORPORASI - Syukron M (Sosio Akademika, 2022)
Nowadays corporations have mushroomed in Indonesia and often cause prolonged problems, especially related to corporate crimes in which these crimes are committed because of the desire of corporations to gain maximum profits because corporations that commit corporate crimes use any means for large profits or profit oriented. As for corporate crimes that are often committed by corporations in the form of corporate crime, namely crime committed by corporations in the context of seeking profit. With various modus operandi of crimes that are often committed by corporations, namely corporate crimes relating to administration, environment, finance, labor, goods products, and dishonest trading practices. While the research method used is the normative legal method. The legal materials collected are primary, secondary, tertiary legal materials. Analysis of the collected legal material is done by way of inventory, systematize, and interpret, urgency of criminal law reform with the spirit of criminal law reform with a policy approach, which is one of them with criminal law policy, it is expected that the formulation of the provision must be firmly regulated in the future so as to minimize the possibility of corporations freeing themselves from responsibility for crimes committed so that in the future comes responsibility of corporate crime in Indonesia can be upheld to the maximum.